Tahlīl Jaudah Būnūd Ikhtibār al-Lughah al-‘Arabiyah li Ghair al-‘Arab fī Jāmi’ah Hāsyim Asy’arī al-Islāmiyah Tebuireng Jombang fî Ḍau al-Mustawā al-Tafkīr al-‘Ālī - Lailatul Qomariyah; Akhmad Sauqi Ahya (Universitas Yudharta Pasuruan, 2022)
This research aims to analyze the quality of test Arabic as a foreign language (TOAFL) items in Hayim Asy’ari University Tabuireng Jombang of perspective higher order thinking skills. The approach used for this research is qualitative and quantitative. The researcher used the qualitative approach to distribute the question items in terms of the cognitive domain at the higher level in the Arabic language test. Data were taken through documentation of results. The results of this research are: 1) The distribution of the items of this test in terms of the cognitive domain in the level of higher thinking skill is of six classifications that mean remembering, understanding, applying, analyzing, evaluating, and creating: 2) Their quality in terms of difficulty coefficient did not meet the criteria of good test items. Because there is no moderation in the number of questions from the level, and as for their quality from the discrimination coefficient, there is a single question that must be eliminated and replaced with new questions.